Proportions des tissus des dents déciduales chez deux individus de Dordogne (France) : l’enfant néanderthalien du Roc de Marsal et le spécimen du Paléolithique supérieur final de La Madeleine. - Priscillia Bayle (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Recent advances in the application to the human fossil record of high-resolution microtomographic analytical techniques allow the noninvasive quantitative characterization of the inner dental structure. Compared to the extant human condition, Neanderthal permanent molars show comparable relative enamel volumes, but distributed over a greater dentine surface. However, deciduous dental tissue proportions in Neanderthals, notably those of the anterior teeth, are still poorly known, and the structural condition characteristic of the anatomically modern fossil human teeth is unreported yet.By means of high-resolution industrial (µCT) and synchrotron radiation (SR-µCT) microtomography, we investigated, for the first time, the inner structure of the entire deciduous dental sequence of the Neanderthal child of Roc de Marsal (Dordogne) and of the late Upper Paleolithic specimen from La Madeleine (La Madeleine 4, Dordogne), and comparatively quantified their volumetric dental tissue proportions.Results show that, since the early developmental stages, Neanderthal teeth (here represented also by isolated specimens from the site of La Chaise, in Charente) are characterized by a unique tissue organization, while the late Upper Paleolithic specimen shows a pattern similar to the extant human condition illustrated by our reference sample.